Effects of elevated soil CO2 concentration on growth and competition in a grass-clover mix - Smith, Karon L.; Lake, Janice A.; Steven, Michael D.; Lomax, Barry H. (Elsevier, 2016)
To investigate potential environmental affects in the context of carbon dioxide (CO2) leakage from Carbon Capture and Storage (CCS) schemes. The ASGARD (Artificial Soil Gassing and Response Detection) facility was established, where CO2 can be injected into the soil in replicated open-air field plots. Eight plots were sown with a grass-clover mix, with four selected for CO2 treatment while four were left as controls. Observations of sward productivity throughout the study allowed three effects to be distinguished: a direct stress response to soil gassing, limiting productivity in both species but with a greater effect on the clover; competition between the grass and clover affected by their differential stress responses; and an overall temporal trend from dominance by clover to dominance by grass in CO2 treatments. The direct effect of soil CO2 (or associated oxygen (O2) deprivation due to the high levels of CO2 in the soil) gave estimated reductions in productivity of 42% and 41% in grass, compared to 66% and 32% for clover in the high and low CO2 gassed zones respectively. Canopy CO2 increased by 70 parts per million (ppm) for every 1% increase in soil CO2 and a significant positive response of stomatal conductance in clover was observed; although carbon acquisition by the plants should not therefore be impeded, the reduction in productivity of the gassed plants is indicative of carbon-based metabolic costs probably related to soil CO2 affecting root physiology. Biomass measurements made after gassing has ceased indicated that recovery of vegetation was close to complete after 12 months.